Faber Salisburgi: Festschrift für Wilfried K. Kovacsovics zum 65. Geburtstag - Kastler, Raimund; Lang, Felix; Wendling, Holger (Archaeo plus, 2018)
Schriftverzeichnis von Wilfried K. Kovacsovics Seite 21-32